Da inexecutividade da decisão declaratória - Maekava, Georgia Sonoe (2019)
This study aims at analyzing the statutory amendment which introduced Article 475-N, I of the 1973 Code of Civil Procedure (Law # 11232/2005), followed by Article 515, I of the 2015 Code of Civil Procedure (Law # 13105/2015), addressing the par excellence enforceable title, the enforceable judgment. The goal is to investigate the interpretation given by legal scholars and case law on the subject, notably the construction of the thesis attaching enforceability to declaratory court decisions and to decisions on prayer to dismiss. To this end, this study addresses judicial decisions, mainly their classification and the concept shaped by each kind of judicial decision. Then, narrowing down the subject, this study analyzes the entire contention involving the enforcement of declaratory decisions, in order to, in the end, deal with the enforceability of the decision to dismissal and its effects on the procedural system, if such phenomenon is admitted